1986
DOI: 10.1039/p29860001631
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic substitution of benzyl benzenesulphonates with anilines in methanol-acetonitrile mixtures. Part 2. Variation in transition-state structure

Abstract: Nucleophilic substitution reactions of benzyl benzenesulphonates (YC6H,CH20S02C6H,Z) with anilines (XC,H,NH,) have been studied in a series of methanol-acetonitrile mixtures. A more electron-donating substituent in the nucleophile ( X = p -M e O ) and a more electron-withdrawing substituent in the leaving group (Z = rn-NO,) led t o an increase in the rate and t o a later transition state with a longer substrate-leaving group bond and a shorter nucleophile-substrate bond. A n electron-withdrawing substituent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is natural that good linear correlations (r > 0.99) are also observed between logarithms of the rate con stants of enzymatic oxidation [9] and nucleophilic substitution [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is natural that good linear correlations (r > 0.99) are also observed between logarithms of the rate con stants of enzymatic oxidation [9] and nucleophilic substitution [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…The rate constants (k 2 ) of the nucleophilic substi tution reactions with anilines in methanol acetonit ryl mixtures (СH 3 CN, 50 →100%) at 35°С [16] (Equation 7), the aminolysis constants (k 2 , k XY , k XZ ) of benzoic anhydrides in methanol at 25-45°С [17] (Equations 8 and 9), and the rate constants of trans 3 nitrophenyl β chlorovinyl ketone with anilines (X = 4 MeO, 4 Me, 3 Cl) in isopropanol at 25°С [18] also appeared to linearly correlate (r = 0.97-0.99) with both the constants of the complex forma tion between anilines and Zn TPhP in chloroform at 25°С and shifts of absorption maxima (Δλ) of MP in ES during the coordination (Scheme 2). Furthermore, the linear correlations between logK, logk, pK a , and Δλ and σ -and σ + constants are observed at the stage of the interaction between cpd II horseradish peroxidase (k in Table 1; Scheme 1, Equation 6 [8]) and anilines containing substituents in the 3 and 4 positions of the benzene ring (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the rate constants k for nucleophilic substitution by anilines in methanolacetonitrile mixtures (50-100%) at 35°C [17] [Eq. (3)], rate constants k 2 , k XY , and k XZ for the aminolysis of benzoic anhydrides in methanol at 25-45°C [18] [Eq.…”
mentioning
confidence: 99%